Using Internet videos to learn about controversies: Evaluation and integration of multiple and multimodal documents by primary school students. (April 2020) - Salmerón, L.; Sampietro, A.; Delgado, P.
Abstract: In many Internet videos authors appear in front of the camera to present their particular view on a topic. Given the high consumption rate of Internet videos by teenagers, we explored the pros and cons of using these videos to learn about complex topics, compared to learning from textual web pages. Specifically, we studied how 207 primary school students (grades 4–6) evaluated and integrated multiple and multimodal web pages (text or video) while learning about the pros and cons of bottled water. Results showed no major role of modality in students' source memory, as measured by citations in their responses to an integration question and their memory for sources. Nevertheless, modality exerted a strong influence on students' beliefs about the topic because, after the study period, they defended the views described in the videos more than those presented in texts. Finally, modality tended to influence students' integration, with participants who learned from two textual webpages including almost twice as many inferences in their responses as those who learned from two videos. We discuss the results in light of current theories of evaluation and integration of multimodal information and (shallow) digital reading, and we elaborate on the pros and cons of using Internet videos in Primary School. Highlights: Primary school students watched Internet videos and read textual Web pages about a controversy. Modality played no major role in students' source memory. Internet videos exerted a strong influence on students' beliefs about the topic. Textual web pages tended to improve students' integration.